Cheap Credit, Lending Operations, and International Politics: The Case of Global Microfinance - GARMAISE, MARK J.; NATIVIDAD, GABRIEL (Journal of Finance, 2013)
ABSTRACT The provision of subsidized credit to financial institutions is an important and frequently used policy tool of governments and central banks. To assess its effectiveness, we exploit changes in international bilateral political relationships that generate shocks to the cost of financing for microfinance institutions (MFIs). MFIs that experience politically driven reductions in total borrowing costs hire more staff and increase administrative expenses. Cheap credit leads to greater profitability for MFIs and promotes a shift toward noncommercial loans but has no effect on total overall lending. Instead, the additional resources are either directed to promoting future growth or dissipated.